A Rebalancing Act for China and Africa : The Effects of China's Rebalancing on Sub-Saharan Africa's Trade and Growth - Nord, Roger (Departmental Papers; Departmental Paper ;, 2017)
How does China's new growth model affect sub-Saharan Africa? To address this question, this paper first looks at the growing ties between China and Africa; attempts to estimate more precisely the impact on growth through the trade channel; and finally draws some policy implications regarding whether this means an end of the Africa Rising narrative or merely the beginning of a new chapter.